Propuesta metodológica para la planificación Del diseño arquitectónico de edificios Multifamiliares sustentables de cuatro pisos - Aguirre Benalcázar, Segundo (2017)
"Housing development has been the driving force behind creation and growth in cities around the world" (Reyes, Sacoto, & Vélez, 2015, p.30), since housing has ceased to be a simple shelter from the climate and The external agents, becoming, above all, a unique space that generates harmony and happiness, making life meaningful. Since the twentieth century, cities have grown according to a modern urban model, which has revalued traditional cities, giving greater use to land and infrastructure and considering as a priority the culture and identity of each city; An architectural culture that as such, seeks to design within the principles of media economics and exploitation of local resources (Durán, 2015).